2002
DOI: 10.1053/joca.2001.0496
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction-enhanced X-ray imaging of articular cartilage

Abstract: DEI is capable of imaging articular cartilage in disarticulated, as well as in intact joints. Gross cartilage defects, even at early stages of development, can be visualized due to a combination of high spatial resolution and detection of X-ray refraction, extinction and absorption patterns. Furthermore, DE images displaying contrast heterogeneities indicative of cartilage degeneration correspond to the degeneration detected by gross and histological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 22 publications
2
114
0
4
Order By: Relevance
“…PCI has been previously demonstrated as a promising image acquisition modality for visualizing structural details of the cartilage matrix with high spatial resolution [12][13][14]. Coan et al acquired PCI-CT images of human knee patellae and reported differences between chondrocyte organization in the radial zone of normal and osteoarthritic cartilage matrix [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCI has been previously demonstrated as a promising image acquisition modality for visualizing structural details of the cartilage matrix with high spatial resolution [12][13][14]. Coan et al acquired PCI-CT images of human knee patellae and reported differences between chondrocyte organization in the radial zone of normal and osteoarthritic cartilage matrix [14].…”
Section: Discussionmentioning
confidence: 99%
“…The phase-contrast effect associated with such refraction can be more pronounced than conventional absorption contrast, specifically for the energy range of X-rays used in diagnostic modalities, and for soft tissue types encountered in clinical practice [9]. This allows PCI to be effective in imaging tissue types where conventional absorption contrast is insufficient for soft tissue characterization, notably in breast [10,11] and cartilage imaging [5,[12][13][14]. Among the different PCI techniques, we specifically focus on the analyzer-based imaging (ABI) method [8,15,16], which has been applied in both ex vivo and in vivo cartilage studies and demonstrated greatly improved cartilage visualization [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Such methods have been used on cartilage before, often on thicker human cartilage samples [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative assessment of the softening of artC is of vital importance for preventing OA and evaluating the progress of cartilage regeneration. Various kinds of non-invasive imaging techniques, including diffraction-enhanced x-ray (Mollenhauer et al 2002), microscopic MRI (Xia et al 2001) and ultrasound (US) (Zheng et al 2001), have been emerged to provide visual diagnosis of artC in the past decade. However, these techniques are not able to indicate the early degeneration of artC.…”
Section: Introductionmentioning
confidence: 99%